Networked publics - Varnelis, Kazys (MIT Press, 2008)
Looking at how maturing digital media and network technologies are transforming place, culture, politics and infrastructure in our everyday life this book provides a synoptic overview as well as illustrative case studies.
Product of a fellowship program at the Annenberg Center for Communication at the University of Southern California, 2005-2006.
Keywords: Internet -- Social aspects -- United States.; Internet -- Political aspects -- United States.; Online social networks -- United States.; Convergence (Telecommunication); USA.; United States.; elektronické knihy; electronic books